2009
DOI: 10.3164/jcbn.08-254
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Murine Double Minute 2 (MDM2) on Helicobacter pylori-Infected Intestinal Metaplasia and Gastric Cancer

Abstract: Summary The overexpression of murine double minute 2 (MDM2) is found in several human tumors, and increased expression of MDM2 inactivates the apoptotic and cell cycle arrest function of p53. Interleukin-16 (IL-16) is a pleiotrophic cytokine and the properties of IL-16 suggest that it involve in the pathophysiological process of chronic inflammatory diseases. In this study, we investigated the expression of MDM2 in intestinal metaplasia and gastric cancer as well as the effect of H. pylori infection and IL-16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…The detailed mechanism has been recently reported with regard to murine double minute 2 (MDM2) which binds to the tumor suppressor p53 and inhibits p53-mediated transactivation. Nakajima et al [49] has found that MDM2 expression is higher in biopsy specimens of intestinal metaplasia and gastric cancer than that of chronic gastritis in H. pylori-infected stomach and that interleukin-16 (IL-16), a T-cell chemoattractant that has been shown to be involved in H. pylori-induced gastric inflammation, increased the expression of MDM2 and cell proliferation of a gastric cancer cell line. Since the overexpression of MDM2 has been shown in several human tumors, and increased expression of MDM2 inactivates the apoptotic and cell cycle arrest function of p53, the expression of MDM2 in long-term H. pylori-infected gastric mucosa may indicate a risk for carcinogenesis, and IL-16 secretion in H. pylori-infected mucosa is one of the factors for gastric carcinogenesis.…”
Section: Gastro-protective Drugsmentioning
confidence: 99%
“…The detailed mechanism has been recently reported with regard to murine double minute 2 (MDM2) which binds to the tumor suppressor p53 and inhibits p53-mediated transactivation. Nakajima et al [49] has found that MDM2 expression is higher in biopsy specimens of intestinal metaplasia and gastric cancer than that of chronic gastritis in H. pylori-infected stomach and that interleukin-16 (IL-16), a T-cell chemoattractant that has been shown to be involved in H. pylori-induced gastric inflammation, increased the expression of MDM2 and cell proliferation of a gastric cancer cell line. Since the overexpression of MDM2 has been shown in several human tumors, and increased expression of MDM2 inactivates the apoptotic and cell cycle arrest function of p53, the expression of MDM2 in long-term H. pylori-infected gastric mucosa may indicate a risk for carcinogenesis, and IL-16 secretion in H. pylori-infected mucosa is one of the factors for gastric carcinogenesis.…”
Section: Gastro-protective Drugsmentioning
confidence: 99%
“…The expression of MDM2 is linked to gain-of-function mutations in many tumors [34]. In addition, the inhibition of MDM2 was shown to block tumor growth or induce cell apoptosis in a number of tumors [35][36][37][38][39]. In addition, DNA amplification of BIRC3 has been observed in mouse liver and human lung cancers, liver carcinoma, oral squamous cell carcinoma, medulloblastoma, glioblastoma and pancreatic cancer [40].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous studies have suggested that the expression of mdm2 increases in gastric carcinoma (36,37). Nakajima et al (3) reported that expression of the mdm2 protein increased not only in gastric cancer, but also in intestinal metaplasia as compared to chronic gastritis. A distinct mdm2 expression was observed in our study, indicating the precancerous nature of AIM more accurately than mucous classification.…”
Section: Discussionmentioning
confidence: 99%